RETRACTED: Development of new technology S4S (Star for Study) for teaching IT sphere students - Zokirov Sanjar; Rakhmatova Gavkharoy (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001